Scientific writing and referee professional training - Argota, G. (Cuban Journal of Agricultural Science, 2023)
Several researchers refer the determining function of the scientific writing in the reflexive construction of knowledge (Chun et al. 2022). The scientific writing, as being a complex process because its style and impact of the results (Lu et al. 2019, Chen et al. 2020 and Ante 2022), require clarity and precision in the information, abilities that with frequency are loss when it is not answer to the research question during the writing process (Simón et al. 2020). In consequence, in the scientific field, the feasible, the ethical, the interest, the discoveries and the relevance as criteria to be measure, influence on the decisions of accepting or rejected a paper which is subjected to a checking process for their publication. From this perspective, the referee represents one of the attention centers due to the decision they emit in the publishing process, whose responsibility is to keep the quality and integrity of the scientific literature (Grimaldo et al. 2018 and Libby et al. 2022).